Discursive psychological analysis on the construction and performance of identity through rights talk on social media related to #FeesMustFall - Mashaba, Tumelo Thabo (Rhodes University, Faculty of Humanities, Department of Psychology, 2019)
#FeesMustFall emerged at the end of 2015 after an announcement that tuitions would increase. The student protests occurred across higher education institutions within the country in which mass shutdowns were initiated, there was the presence of violence and the use of social media. The protests occurred in 2016 but experienced a shift in tone in terms of the violence present in the protests. The research sought to unpack how identity was constructed and performed through rights talk in regards to #FeesMustFall on social media. The methodology worked from a social constructionist perspective where the research consisted of a discursive psychological analytical approach to the texts presented. The discursive repertoires that were identified were: emotions repertoire; struggle repertoire; apartheid repertoire; racial repertoire; and rights repertoire. The subject positions revealed through the repertoires indicated that protesters and supporters constructed and performed their identity in particular ways. They were positioned as black; working class; victims who are enacting a sense of agency; denied their rights; have moral authority and are a parallel to the protesters under apartheid. The repertoire of struggle, racial and apartheid all link with each other. The rights repertoire is the foundation and the emotions repertoire is the tone of the student protests.
Keywords: Identity; Right to education; Human rights; Social media -- Political aspects -- South Africa; College students -- Political activity -- South Africa; College students -- Attitudes -- South Africa; College students, Black -- Psychology -- South Africa; College students, Black -- Attitudes -- South Africa; College students -- Psychology -- South Africa; Student protestors -- Attitudes -- South Africa; Student movements -- South Africa; Internet and activisim -- South Africa; Internet in political campaigns -- South Africa; Higher education and state -- South Africa